A Structural Framework for Developing Self-emulsifying Drug Delivery System through Quality by Design Approach - Kavitha, A. N. (Asian Journal of Pharmaceutics (AJP), 2020)
In recent years, drug discovery studies show that more than 40% of new drugs synthesized are having poor aqueous solubility rendering them poorly bioavailable after oral administration. Self-emulsifying drug delivery systems (SEDDS) are the novel lipid-based formulations having the potential to enhance the oral bioavailability of poorly water-soluble drugs which belong to class II and IV of the biopharmaceutical classification system. SEDDS is the isotropic mixtures of oil, surfactant, cosurfactant, and sometimes cosolvent. The presence of surfactant enhances the membrane permeability, whereas medium- and long-chain triglyceride oils promote the lymphatic absorption of the drug. The better performance of SEDDS in terms of improvement in solubility and permeability characteristics has rapidly introduced many SEDDS products into the market and many others in the clinical development phase. Quality by design (QbD) is a regulatory-driven approach, which adopts a multitude of techniques in product development, which lends a controlled and reproducible result, thereby resulting in a formulation which could meet the therapeutic goals. The complexities of the SEDDS formulation and the ingredients involved in the design of experiment and risk assessment techniques based on QbD methodologies are increasingly used in the formulation development of SEDDS. This review provides a summary of the systematic application of QbD concepts in the development of SEDDS for poorly bioavailable drugs.